Non Verbal Signs of Marshmello Feat Bastille’s Music Video “Happier” - Ni Putu Era Puspita Yanthy; I Nyoman Udayana; Ni Ketut Sri Rahayunu (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The title of this study is non verbal signs in Marshmello feat Bastille’s music video “Happier”. This study focused on the analysis of the non-verbal signs found in Marshmello feat Bastille’s music video “happier”. There are two aims of this study. First, it is to identify non-verbal signs in the music video. Second, it is to analyze and explain the non verbal signs found in the music video. The data in this study were in the form of image taken from snapshot of the music video. In this study, there were ten image snapshots that will be discussed. In this study, the method to collect the data were documentation. The data relating with the image snapshots were analyzed qualitatively based on the theory of verbal and non-verbal signs by Dyer. It is also supported by the theory of color meaning by Oleson. The result shows that almost all the non-verbal elements and can be found in the music video. Only three elements which are national and racial, cropping, and special effects were not used in the music video. It shows that the music video doesn’t use any racial stereotypical nor it used any special effects and cropping technique to make the music video more dynamics and draw the attention to certain part of the body.